Life Cycle Analysis of Coal and RDF Utilization as Energy Sources for Industry: A Comparative Study of Environmental Impacts - Nurseta, Dimastyaji Yusron; Bigita, Adora Salsa; Damayanti, Alvina; Nugroho, Aprianto Tyas Dwi; Andini, Aulia Mutiara; Firdausi, Bq. Nurul Maghfira Agni; Wati, Hessy Rahma (Universitas Diponegoro, 2025)
This study utilized an LCA approach to comparatively analyze the environmental impact of using coal and RDF as industrial energy sources. Coal, which constitutes the foundation of Indonesia's economy and its primary energy source, has resulted in substantial emissions. In response to this challenge, RDF has emerged as a promising alternative fuel made from municipal waste with a calorific value equivalent to coal. The findings of this research consistently demonstrate that RDF exhibits a considerably diminished environmental impact profile in comparison to coal, across a wide range of evaluated impact categories. For instance, RDF contributes a mere 2% to terrestrial and freshwater aquatic ecotoxicity, whereas coal contributes 98%. RDF exhibits a minimal contribution to acidification potential, eutrophication, ozone depletion, and human toxicity. The novelty of this research lies in its in-depth comparative analysis of the environmental impacts of coal and RDF using LCA with gate-to-gate boundaries, as well as the identification of key impact points (hotspots) in each energy production process. These findings serve to reinforce the argument that RDF is a more sustainable and environmentally friendly energy option for Indonesia's industrial sector.